Successful Treatment of Whole Coronary Artery Spasm after Off-Pump Coronary Artery Bypass Grafting - Akihiro Kobayashi; Yoshimori Araki; Takafumi Terada; Osamu Kawaguchi (Case Reports in Cardiology)
Coronary artery spasm after coronary artery bypass grafting is a rare but life-threatening condition. Herein, we report the case of a 77-year-old man who received off-pump coronary artery bypass grafting. An hour after surgery, there was a sudden hemodynamic compromise due to coronary artery spasm, prompting emergent coronary angiography with extracorporeal membrane oxygenation support. Because the angiography results showed diffuse severe spasm of the entire native coronary artery, the patient was treated with an intracoronary injection of vasodilators. The patient recovered in 7 days with mechanical support, catecholamines, and vasodilators, and he was discharged on postoperative day 30. Although coronary artery spasm after off-pump coronary artery bypass surgery is a rare condition, it must be suspected when sudden circulatory collapse occurs.